MOLECULAR MODELLING, QSAR AND PHARMACOPHORE STUDIES ON ANTI-VIRAL, ANTI-MALARIAL AND ANTI-INFLAMMATORY BIOACTIVE COMPOUNDS FROM MARINE SOURCES - Karthiga Devi, Seenivasan; Velmurugan, Devadasan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Methyltransferase, human dihydrofolate reductase, and acidic mammalian chitinase are the potential targets for the viral, malarial and inflammatory diseases, respectively. Hence, it is of interest to screen the natural compounds against these proteins using molecular docking. In this study, pharmacophore modeling was performed on marine compounds against these diseases using PHASE module. This resulted in the common pharmacophore hypothesis AADRR.7f, which might be responsible for the biological activity: Two acceptor (A) groups (âˆ’C=O), one donor (O-H) and two aromatic rings (R). The three-dimensional-quantitative structure activity relationship model obtained has the correlation coefficient values q2=0.67; pred r2=0.86. In addition, molecular docking studies were performed. The model developed may serve as a query tool for future virtual screening and drug designing for these targets. Marine compounds from the different marine sources such as alga, bacterium, sponges, soft corals, sea cucumber, and clam have been selected from the literature. Keywords: Molecular modeling, Quantitative structure activity relationship, Pharmacophore, Methyltransferase, Human dihydrofolate reductase, Acidic mammalian chitinase, Absorption, distribution, metabolism and excretion, Docking, Structure based drug design.